Biomechanical evaluation of a novel suturing scheme for grafting load-bearing collagen scaffolds for rotator cuff repair - Islam, Anowarul (Clin Biomech (Bristol, Avon), 2015)
BACKGROUND: Currently, there are no well-established suture protocols to attach fully load-bearing scaffolds which span tendon defects between bone and muscle for repair of critical sized tendon tears. Methods to attach load-bearing tissue repair scaffolds could enable functional repair of tendon injuries. METHODS: Sixteen rabbit shoulders were dissected (New Zealand white rabbits, 1 yr. old, female) to isolate the humeral-infraspinatus muscle complex. A unique suture technique was developed to allow for a 5 mm segmental defect in infraspinatus tendon to be replaced with a mechanically strong bioscaffold woven from pure collagen threads. The suturing pattern resulted in a fully load-bearing scaffold. The tensile stiffness and strength of scaffold repair was compared with intact infraspinatus and regular direct repair. FINDINGS: The failure load and displacement at failure of the scaffold repair group were 59.9 N (Standard Deviation, SD = 10.7) and 10.3 mm (SD = 2.9), respectively and matched those obtained by direct repair group which were 57.5 N (SD = 15.3) and 8.6 mm (SD = 1.5), (p > 0.05). Failure load, displacement at failure and stiffness of both of the repair groups were half of the intact infraspinatus shoulder group. INTERPRETATION: With the developed suture technique, scaffolds repair showed similar failure load, displacement at failure and stiffness to the direct repair. This novel suturing pattern and the mechanical robustness of the scaffold at time zero indicates that the proposed model is mechanically viable for future in vivo studies which has a higher potential to translate into clinical uses.